The Effect Of Question And Answer Method On Students’ Speaking Ability At SMP Y.P KELUARGA Pematangsiantar - Natanael Saragih; Nadya Ikhwana Maisyaro Lubis (Program Studi Pendidikan Bahasa Inggris FKIP, 2022)
This research entitled The Effect of Quesstion and Ansmwer Method On Students’ Speaking Ability At SMP Y.P Keluarga Pematangsiantar. It concered with the problem: Does Q & A method affect students’ speaking ability of grade VII SMP Y.P Keluarga Pematangsiantar on the academic year 2021/2022? to answer the research, some theories are used: Andriyani (2015), Ikramuddin in Sukriyanto (2017), Hormalis in Hrahap (2015), Sudjono (2017).The research design was a pre - experimental research. the sample was choosen by simple random sampling. It involved 46 students. The result showed that by using Question and Answer method has improved the students’ speaking ability. The improvement of students achievement are proved from Pre-test and Post - test result. The mean score of post - test (74,17) was higher than score of pre - test (51). The result also showed that standard deviation in pre-test (10,24) while in post - test (12,10). It could be concluded that there was a significant effect of question and answer method on students’ speaking ability at seventh grade of SMP Y.P Keluarga Pematangsiantar in academic year 2021/2022